Design and Analysis of Printed Yagi-Uda Antenna and Two-Element Array for WLAN Applications - Cai Run-Nan; Yang Ming-Chuan; Lin Shu; Zhang Xing-Qi; Zhang Xin-Yue; Liu Xiao-Feng (International Journal of Antennas and Propagation)
A printed director antenna with compact structure is proposed. The antenna is fed by a balanced microstrip-slotline and makes good use of space to reduce feeding network area and the size of antenna. According to the simulation results of CST MICROWAVE STUDIO software, broadband characteristics and directional radiation properties of the antenna are explained. The operating bandwidth is 1.8 GHz–3.5 GHz with reflection coefficient less than −10 dB. Antenna gain in band can achieve 4.5–6.8 dBi, and the overall size of antenna is smaller than 0.34λ0×0.58λ0. Then the antenna is developed to a two-element antenna array, working frequency and relative bandwidth of which are 2.15–2.87 GHz and 28.7%, respectively. Compared with antenna unit, the gain of the antenna array has increased by 2 dB. Thus the proposed antenna has characteristics of compact structure, relatively small size, and wideband, and it can be widely used in PCS/UMTS/WLAN/ WiMAX fields.